PROFILE OF MICROORGANISMS CAUSING VAGINAL DISCHARGE IN REPRODUCTIVE WOMEN AT DR. PIRNGADI HOSPITAL IN MEDAN - Iqrina Widya Zahara; Irma Damayanti Roesyanto; Sri Amelia (Buletin Farmatera, 2020)
Leucorrhoea or Fluor albus or leukorrhea vaginal discharge is the discharge of fluid other than blood from the vaginal canal out of the ordinary, either smelling or not, and accompanied by local itching. There are two factors that cause leucorrhoea, namely endogenous factor such as abnormalities in the vagina and exogenous factor which are infection and non-infection. The aim of this study is to find the profile of microorganisms causing vaginal discharge in reproductive women. This is a descriptive study with cross-sectional method conducted at the Skin and Genital Polyclinic of the Sexually Transmitted Infectious Disease Division and the Obstetrics and Gynecology Clinic of Pirngadi Hospital, Medan. Populations that have met the inclusion and exclusion criterias were included in the study. Vaginal discharge samples will be sent to the microbiology laboratory and the parasitology laboratory of faculty medicine of University of North Sumatera to examine the gram staining, KOH staining, bacterial and fungal cultures and wet preparations for parasites. Out of a total of 50 people, the majority of the sample are in aged 31-40 years, with a history of high school education and working women. The most types of vaginal discharge are pathological (84%) and the most common cause of vaginal discharge is a fungal infection by Candida sp (90%) followed by bacterial infection by Staphylococcus aureus (64.8%) and Klebsiella (20.3%)